Tutorial: Designing immersive VR systems: from bits to bolts - Soares, L. P.; Jorge, J.; Dias, J.; Lin, M.; Raposo, A. (Atas da Conferência IEEE VR 2010, 2010)
Immersive environments have become affordable for many research centers. However, a complete solution needs several integration steps to be fully operational. Some of these steps are difficult to accomplish and require an uncommon combination of different skills. This tutorial presents the most recent techniques developed from display to software tools. The hardware in a typical VR installations combines projectors, screens, speakers, computers, tracking and I/O devices. The tutorial will discuss hardware options, explaining their advantages and disadvantages. We will cover design decisions from basic software and hardware design, through user interfaces and acoustical rendering to how to administrate the whole solution. Additionally we provide an introduction to tracking systems, explaining how the most common devices work. Finally we briefly cover integration software and middleware developed for most settings.